2017
DOI: 10.1111/eva.12500
|View full text |Cite
|
Sign up to set email alerts
|

Evolved pesticide tolerance influences susceptibility to parasites in amphibians

Abstract: Because ecosystems throughout the globe are contaminated with pesticides, there is a need to understand how natural populations cope with pesticides and the implications for ecological interactions. From an evolutionary perspective, there is evidence that pesticide tolerance can be achieved via two mechanisms: selection for constitutive tolerance over multiple generations or by inducing tolerance within a single generation via phenotypic plasticity. While both mechanisms can allow organisms to persist in conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 85 publications
4
39
2
Order By: Relevance
“…These results corroborate previous studies demonstrating the presence of phenotypic costs of tolerance, such as reduced fecundity or survival of tolerant individuals in pesticide‐free environments (Baucom & Mauricio, 2004; Semlitsch et al, 2000). Beyond life history trade‐offs (e.g., survival and reproduction), high tolerance to pesticides has been linked with reduced tolerance to biotic stressors, such as parasites (Hua et al, 2017; Jansen, Stoks, Coors, Doorslaer, & Meester, 2011). Additionally, these findings are coherent with observations from Hua et al (2015), where high plasticity in tolerance was most common in environments where pesticide exposure was likely infrequent or absent (i.e., far from agriculture).…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate previous studies demonstrating the presence of phenotypic costs of tolerance, such as reduced fecundity or survival of tolerant individuals in pesticide‐free environments (Baucom & Mauricio, 2004; Semlitsch et al, 2000). Beyond life history trade‐offs (e.g., survival and reproduction), high tolerance to pesticides has been linked with reduced tolerance to biotic stressors, such as parasites (Hua et al, 2017; Jansen, Stoks, Coors, Doorslaer, & Meester, 2011). Additionally, these findings are coherent with observations from Hua et al (2015), where high plasticity in tolerance was most common in environments where pesticide exposure was likely infrequent or absent (i.e., far from agriculture).…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors also show that adaptation to a pesticide can bear costs, as indicated by increased viral loads following exposure to ranavirus. This work from Hua et al (2017) highlights the need to consider multiple stressors in evolutionary ecotoxicological inquiry and reminds us of the value of studying nontarget species in agricultural contexts, where most of our knowledge about evolution has been limited largely to studies of pest species. Another important takeaway from Hua et al (2017) is that community context matters when assessing the evolutionary impacts of contaminants on a given organism, a point seldom considered in community ecotoxicology.…”
Section: In the Issuementioning
confidence: 96%
“…Attempting to understand this capacity of evolution is a recurrent theme in the papers appearing in this special issue (see especially Whitehead et al 2017). Our ability to gain this understanding will surely improve as we broaden our assessment of evolutionary toxicology beyond the scope of pesticide resistance, and focus on increasingly diverse contexts where nontarget organisms are impacted by the use and distribution of toxic chemicals in the environment (e.g., Hua et al 2017;Whitehead, Clark, Reid, Hahn, & Nacci, et al 2017). Indeed, numerous observations of phenotypic and molecular changes have now been described in wild populations exposed to industrial age chemicals.…”
Section: A Historical Perspective On Evolutionary Toxicologymentioning
confidence: 99%
See 2 more Smart Citations